(untitled) (Agricultural Engineering, 2019)
The article presents structural specifications and conceptual analysis of the test car body equipped with a hybrid power transmission system. The test car is constructed by students of the Faculty of Technical Sciences of the University of Warmia and Mazury in Olsztyn. Works dedicated to designing and construction of a car body aim at the increase of safety and improvement of aesthetics of the constructed vehicle with simultaneous maintenance of its operational and test functionality. The article presents a simplified analysis of the distribution of pressure around the body for several suggested concepts and selected technologies of production of the test car body. The paper presents results of computer simulations, of the pressure distribution and the remaining aspects of assessment of the car body functionality.